Topological Spaces with Skorokhod Representation Property - Banakh, T. O.; Bogachev, V. I.; Kolesnikov, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We give a survey of recent results that generalize and develop a classical theorem of Skorokhod on representation of weakly convergent sequences of probability measures by almost everywhere convergent sequences of mappings.